Photogrammetric data analysis for fortified architecture. Survey of currently disused structures - G. Gioioso; L. Corniello (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The research presents the results of the analysis of coastal cities in Albania, characterised by military bunkers for defensive purposes. The work is divided into an analysis of the researched territories, two-dimensional surveys of the bunkers and their classification into XS, S, M, L, XL with regard to their size, and an applicative conclusion of digital technologies for digital modelling and graphic visualisation of the spaces. These architectures are located along the coastline on steep slopes or, at this time, in the private gardens of summer residences, and this location has greatly influenced the survey campaigns, determining the state of the sites, often in a state of complete abandonment. Some underground structures, such as the one located in the bay of Porto Palermo, are currently in use by the navy for the safekeeping of ships and their maintenance. The final task of the research work is to propose a graphic knowledge of the coastal sites between Vlora and Saranda, which have been the subject of uncontrolled construction of buildings for seaside tourism in the last decade, documenting the state of the sites of defence architecture.